2015
DOI: 10.1002/celc.201500366
|View full text |Cite
|
Sign up to set email alerts
|

Coupling of Independent Electrochemical Reactions and Fluorescence at Closed Bipolar Interdigitated Electrode Arrays

Abstract: Electrochemical reactions occurring at the opposite ends of bipolar electrodes (BPEs) are necessarily coupled, enabling electron transfer events at one end to be read out optically, for example, by coupling to fluorogenic reactions at the other end. To explore the potential of this technique for studying multiple redox events, arrays of parallel BPE interdigitated electrode arrays (IDEAs) were fabricated and integrated with separate analytical and reporter microfluidic channels, respectively, in a closed BPE c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
41
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(43 citation statements)
references
References 44 publications
1
41
1
Order By: Relevance
“…Undoubtedly, the strategy of confining electrochemical polarization inside nanopores provides new insight into the electron‐transfer process between single molecules and nanointerfaces. Further studies have revealed that the polarization of the metal layer inside the pore can lead to various electrochemical responses, such as ion‐current rectification owing to the enhanced concentration of ions in the nanoconfinement . Recently, a 30 nm gold nanotip was rapidly generated inside a nanopore confinement as a confined nanopore electrode (CNE) by a rapid chemical–electrochemical fabrication method.…”
Section: Electrochemical Polarization Inside a Confined Nanopore For mentioning
confidence: 99%
“…Undoubtedly, the strategy of confining electrochemical polarization inside nanopores provides new insight into the electron‐transfer process between single molecules and nanointerfaces. Further studies have revealed that the polarization of the metal layer inside the pore can lead to various electrochemical responses, such as ion‐current rectification owing to the enhanced concentration of ions in the nanoconfinement . Recently, a 30 nm gold nanotip was rapidly generated inside a nanopore confinement as a confined nanopore electrode (CNE) by a rapid chemical–electrochemical fabrication method.…”
Section: Electrochemical Polarization Inside a Confined Nanopore For mentioning
confidence: 99%
“…The most recent BPE approaches explore the possibility to detect multiple redox events and for that purpose, interdigitated bipolar electrode arrays can be readily fabricated and integrated inside several microfluidic channels. This was achieved with model redox probes as well as biorelevant mediators in a closed BPE configuration .…”
Section: Bipolar Electrodes Operating In a Microchannelmentioning
confidence: 99%
“…Massive parallel arrays containing tens to hundreds of thousands c-BPEs can be used and simultaneously monitored using ECL or fluorescence. [24][25][26][27][28] Their utilization has become a unique strategy for monitoring large-scale heterogeneous electron-transfer events. When redox-generated light is used to measure the faradaic response, each electrode in a large array serves as an equivalent optical pixel for wide-scale spatial resolution of electrochemical processes.…”
Section: Introductionmentioning
confidence: 99%